A rapid review of evidence and recommendations from the SIOPE radiation oncology working group to help mitigate for reduced paediatric radiotherapy capacity during the COVID-19 pandemic or other crises. (July 2020) - Janssens, Geert O.; Mandeville, Henry C.; Timmermann, Beate; Maduro, John H.; Alapetite, Claire; Padovani, Laetitia; Horan, Gail; Lassen-Ramshad, Yasmin; Dieckmann, Karin; Ruebe, Christian; Thorp, Nicky; Gandola, Lorenza; et al.
Highlights: No guidelines for the optimal use of paediatric radiotherapy facilities during a shortage. Recommendations for the optimal use of paediatric radiotherapy facilities are presented. This guideline has applications in low and middle income countries with limited resources. Abstract: Objective: To derive evidence-based recommendations for the optimal utilisation of resources during unexpected shortage of radiotherapy capacity. Methods and materials: We have undertaken a rapid review of published literature on the role of radiotherapy in the multimodality treatment of paediatric cancers governing the European practise of paediatric radiotherapy. The derived data has been discussed with expert paediatric radiation oncologists to derive a hierarchy of recommendations. Results: The general recommendations to mitigate the potential detriment of an unexpected shortage of radiotherapy facilities include: (1) maintain current standards of care as long as possible (2) refer to another specialist paediatric radiotherapy department with similar level of expertise (3) prioritise use of existing radiotherapy resources to treat patients with tumours where radiotherapy has the most effect on clinical outcome (4) use chemotherapy to defer the start of radiotherapy where timing of radiotherapy is not expected to be detrimental (5) active surveillance for low-grade tumours if appropriate and (6) consider iso-effective hypofractionated radiotherapy regimens only for selected patients with predicted poor prognosis. The effectiveness of radiotherapy and recommendations for prioritisation of its use for common and challenging paediatric tumours are discussed. Conclusion: This review provides evidence-based treatment recommendations during unexpected shortage of paediatric radiotherapy facilities. It has wider applications for the optimal utilisation of facilities, to improve clinical outcome in low- and middle-income countries, where limited resources continue to be a challenge.